2021
DOI: 10.1108/ijoa-05-2020-2184
|View full text |Cite
|
Sign up to set email alerts
|

Systemic leadership development: impact on organizational effectiveness

Abstract: Purpose This study aims to examine the impact of leadership development programs on organizational outcomes and organizational effectiveness. Design/methodology/approach Using a grounded theory approach, semi-structured interviews were conducted with 15 executive leaders from aviation firms in Brazil with employees participating in a leadership development program. NVivo12 was used for coding and managing the data. Thematic analysis was performed to determine themes and categories. Findings The leadership … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 58 publications
0
14
0
1
Order By: Relevance
“…Organizational effectiveness is defined as the organization's ability to achieve goals through the effective use of resources and continuously adapting to the external environment (Douglas, et al, 2021). Organizational effectiveness reflects how successful the organization is in achieving the desired results (Etzioni, 1964in William, 2019.…”
Section: Organizational Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Organizational effectiveness is defined as the organization's ability to achieve goals through the effective use of resources and continuously adapting to the external environment (Douglas, et al, 2021). Organizational effectiveness reflects how successful the organization is in achieving the desired results (Etzioni, 1964in William, 2019.…”
Section: Organizational Effectivenessmentioning
confidence: 99%
“…Organizational effectiveness reflects how successful the organization is in achieving the desired results (Etzioni, 1964in William, 2019. Organizational effectiveness is based on the ability to survive, achieve goals, and remain fiscally feasible which is achieved through efficient and reliable processes, human resources, and their ability to adapt to the external environment (Yuki, 2008in Douglas et al, 2021. Quinn and Rohrbaugh (1983) mapped organizational effectiveness into a spatial model.…”
Section: Organizational Effectivenessmentioning
confidence: 99%
“…A review of 20 years of empirical studies concerning nonprofit organization effectiveness found that organizational effectiveness, illustrating how effective the organization reaches its goals based on resource allocating and adaptation to the external conditions (Islam, Said, Sumardi, & Rahman, 2020; Douglas, Merritt, Roberts, & Watkins, 2021), was both a powerful and problematic concept (Forbes, 1998). It involved various aspects such as communication effectiveness, decision-making effectiveness (Hagerer, 2019), competing advantages (Jha, 2019) and fulfilling of stakeholders' demands (Thompson, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, organizational leaders must properly guide staff through changes by maintaining their commitment and engagement toward the organization [43,44]. Furthermore, greater organizational effectiveness may be achieved through the alignment of human capital with corporate goals and objectives [17,45].…”
Section: Innovative Leadershipmentioning
confidence: 99%
“…Researching how a holistic approach to leadership can affect organizational effectiveness is necessary, as very little has been done in this respect. Much research to date has been carried out on the outcomes of such leadership for individuals, but not at the organizational level [17], thereby revealing an area of research still to be tackled in real depth on how organizational leadership may be improved and transformed to benefit the organization, as well as the wider society, not just in the short but also in the long term. Such societally conscious approaches with respect to leadership have in the past been largely ignored or bypassed [12], with leadership success being largely measured simply by the pursuit of maximizing profit [10,12,18,19].…”
Section: Introductionmentioning
confidence: 99%